Breaking the Cycle? Intergenerational Effects of an Antipoverty Program in Early Childhood - Barr, Andrew; Gibbs, Chloe R. (Journal of Political Economy, 2022)
Despite substantial evidence that resources and outcomes are transmitted across generations, there has been limited inquiry into the extent to which antipoverty programs actually disrupt the cycle of bad outcomes. We leverage the rollout of the United States’s largest early-childhood program, Head Start, to estimate the effect of early-childhood exposure among mothers on their children’s long-term outcomes. We find evidence of intergenerational transmission of effects in the form of increased educational attainment, reduced teen pregnancy, and reduced criminal engagement in the second generation. These effects correspond to an estimated increase in discounted second-generation wages of 6%–11%, depending on specification. Exploration of earlier outcomes suggests an important role for changes in parenting behavior and potential noncognitive channels.